2019
DOI: 10.1002/ca.23337
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the internal architecture of the superficial part of the masseter muscle in vivo

Abstract: It is unclear whether the deep inferior tendon (DIT) is equally present in vivo, and little anatomical information is available regarding the existence and morphology of the DIT in healthy young subjects. The aim of this study was to characterize the DIT of the masseter muscle in healthy young subjects using ultrasonography and to compare the morphology of this tendon with previously reported data for healthy young subjects in order to provide the most-effective injection methods for botulinum neurotoxin treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…US-guided examinations allow BoNT injections to be performed safely and more effectively than blind injections [16,17]. However, to the best of our knowledge, no previous study has investigated the US-related anatomy of the procerus.…”
Section: Introductionmentioning
confidence: 99%
“…US-guided examinations allow BoNT injections to be performed safely and more effectively than blind injections [16,17]. However, to the best of our knowledge, no previous study has investigated the US-related anatomy of the procerus.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that individual differences in the contractions of the three layers of the masseter result in various types of bulging [ 19 ]. It has also been reported that there is a strong tendinous DIT inside the masseter that may prevent the spread of toxin, as well as individual differences in the morphology of the DIT [ 7 , 20 ]. It can therefore be inferred that imbalance of the contractile capability of the masseter induced by the deep injection method and the diffusion-inhibiting effect of DIT can cause PMB due to excessive contraction of the superficial layer.…”
Section: Discussionmentioning
confidence: 99%
“…Avoiding these side effects requires that practitioners have a thorough understanding of the anatomical locations and morphology of the masseter muscle, the relationship between the masseter and risorius muscle, and related vascular structures [14][15][16][17][18]. Masseteric bulging is another side effect, which is observed in 0.49~18.8% of cases and can often occur 2-4 weeks after a BoNT injection [18][19][20]. If the paradoxical masseteric bulging does not recuperate within two weeks, a superficial BoNT injection into the masseter muscle is usually performed [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, frequent BoNT injections result in the production of antibodies that reduce the treatment's efficacy [22][23][24]. Therefore, various clinical studies have been performed with the aim of identifying BoNT injection points that would avoid masseteric bulging and increase the durability of the treatment effects [20]. These studies of BoNT injections into the masseter muscle have focused on volume changes of the masseter muscle, as evaluated by ultrasonography (US), three-dimensional laser scanning, computed tomography and magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation